2017
DOI: 10.2527/tas2017.0045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agronomic factors on yield and quality of whole corn plants and the impact of feeding high concentrations of corn silage in diets containing distillers grains to finishing cattle1

Abstract: Corn plants were sampled over 2 consecutive years to assess the effects of corn hybrid maturity class, plant population, and harvest time on whole corn plant quality and yield in Nebraska. A finishing experiment evaluated the substitution of corn with corn silage in diets with corn modified distillers grains with solubles (MDGS). The first 2 harvest dates were at the mid- and late-silage harvest times whereas the final harvest was at the grain harvest stage of plant maturity. Whole plant yields increased as ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…In the current study, despite anomalies in some locations, the overall negative correlations between NDFD and DM and starch concentrations, and positive correlations with DMD and NDF concentrations indicate that as the plants matured, NDF concentration declined, but DMD was negatively affected by lower NDFD [42]. This result corroborates the findings of Burken, Nuttelman, Gramkow, McGee, Sudbeck, Gardine, Hoegemeyer, Klopfenstein, and Erickson [27], who reported a decrease of in situ NDF disappearance with progressive maturity. As mentioned by Hunt, Kezar, and Vinande [32] and Johnson, Harrison, Hunt, Shinners, Doggett, and Sapienza [30], selection of high quality silage hybrids should focus on maintaining high grain yields and high fiber digestibility despite advanced stages of maturity.…”
Section: Yield Chemical Composition and Rumen Digestibilitysupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, despite anomalies in some locations, the overall negative correlations between NDFD and DM and starch concentrations, and positive correlations with DMD and NDF concentrations indicate that as the plants matured, NDF concentration declined, but DMD was negatively affected by lower NDFD [42]. This result corroborates the findings of Burken, Nuttelman, Gramkow, McGee, Sudbeck, Gardine, Hoegemeyer, Klopfenstein, and Erickson [27], who reported a decrease of in situ NDF disappearance with progressive maturity. As mentioned by Hunt, Kezar, and Vinande [32] and Johnson, Harrison, Hunt, Shinners, Doggett, and Sapienza [30], selection of high quality silage hybrids should focus on maintaining high grain yields and high fiber digestibility despite advanced stages of maturity.…”
Section: Yield Chemical Composition and Rumen Digestibilitysupporting
confidence: 88%
“…Daynard and Hunter [24] observed that CS yield was close to maximum at 300 g kg −1 DM. In more suitable growing areas, Lewis, Cox and Cherney [25] reported a CS yield of 13.6 Mg ha −1 in New York State and Burken et al [27] reported 22.8 Mg ha −1 for Nebraska.…”
Section: Maturity Location and Yieldmentioning
confidence: 99%
“…Maximum DM yield was achieved when whole-plant DM reached 42% DM, which occurred at the latest date the researchers harvested. Burken et al (2017a) harvested corn plants at three different time points coinciding with traditional silage harvest with a whole-plant DM of 35.8%, physiological maturity with a whole-plant DM of 42.4%, and corn grain harvest. In year 1 of the experiment, stover yield and whole-plant yields responded in a quadratic fashion with both stover and whole-plant yields maximized at physiological maturity and decreased at corn grain harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, source and amount of supplemental protein are important factors affecting growth because supplemental protein provides a significant amount of the total dietary protein ( Felix et al, 2014 ). When corn silage replaces corn in finishing diets, gain-to-feed ratio (G:F) decreases as corn silage increases in the diet ( Goodrich et al, 1974 ; Burken et al, 2017a ). Management decisions, such as silage harvest maturity, can affect the quality and yield of corn silage and impact performance in growing and finishing cattle ( Chamberlain et al, 1971 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation